2012
DOI: 10.1186/2043-9113-2-12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autoclaving and high pressure on allergenicity of hazelnut proteins

Abstract: BackgroundHazelnut is reported as a causative agent of allergic reactions. However it is also an edible nut with health benefits. The allergenic characteristics of hazelnut-samples after autoclaving (AC) and high-pressure (HHP) processing have been studied and are also presented here. Previous studies demonstrated that AC treatments were responsible for structural transformation of protein structure motifs. Thus, structural analyses of allergen proteins from hazelnut were carried out to observe what is occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 59 publications
9
33
0
Order By: Relevance
“…As for Cor a 1, the allergenicity of Cor a 8 was significantly affected when submitting hazelnuts to high temperatures and wet processing, such as autoclave (121ºC and 138ºC, for 15 and 30 min), since autoclaving induces the disorganisation of almost all possible epitopes in this protein. The application of high pressure processing (300 to 600 Mba) to hazelnut samples did not affect the IgE-binding capacity of Cor a 8 in the test population (López et al, 2012). Like the profilins, the nsLTP are also considered pan-allergens, suggesting that these proteins are well spread throughout the nature.…”
Section: Cor a 8 (Nsltp)mentioning
confidence: 91%
See 3 more Smart Citations
“…As for Cor a 1, the allergenicity of Cor a 8 was significantly affected when submitting hazelnuts to high temperatures and wet processing, such as autoclave (121ºC and 138ºC, for 15 and 30 min), since autoclaving induces the disorganisation of almost all possible epitopes in this protein. The application of high pressure processing (300 to 600 Mba) to hazelnut samples did not affect the IgE-binding capacity of Cor a 8 in the test population (López et al, 2012). Like the profilins, the nsLTP are also considered pan-allergens, suggesting that these proteins are well spread throughout the nature.…”
Section: Cor a 8 (Nsltp)mentioning
confidence: 91%
“…Preliminary studies on raw hazelnuts submitted to dry heat treatment at 170ºC, indicated that the protein profile and the amount of Cor a 9 was not affected until after 20 min of roasting (Dooper et al, 2008). More recently, López et al (2012) verified that Cor a 9 is a highly well-structured protein, enriched by a beta-sheet core and with long unstructured loops. Those loop regions are estimated not to be modelled due to their lack of stable structure, but they are predicted to exhibit linear epitopes located at the external faces of the protein and thereby being exposed to solvent.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations
“…So far, only a few papers were reported on the evaluation of food processing effects on hazelnut proteins, and most of them focused on the fate of allergenic proteins upon thermal treatment. In particular, Cor a 1, Cor a 2, and Cor a 8 were proved to be thermolabile proteins [40][41][42], whereas Cor a 9 and Cor a 11 allergens were considered more thermostable [43][44][45]. In addition, Cor a 9 and Cor a 11, under particular processing condition, could generate Maillard reactions and advanced glycation end products [44,45].…”
Section: Varietal Diversity Andmentioning
confidence: 99%